Comparison of the Effectiveness between Povidone-Iodine and Bleomycin as Pleurodesis Agents in Patients with Malignant Pleural Effusion at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Tri Wahyu Murni; Euis Maryani; Try Sutrisno Rahantan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Malignant pleural effusion (MPE) is a clinical problem in which fluid accumulates in the pleural cavity. This condition is generally caused by malignancy. Pleurodesis is a medical procedure in the form of fusion of the visceral and parietal pleura in order to prevent the recurrence of pleural effusion. Pleurodesis has the risk of causing chronic inflammation, which will trigger excessive attachment between the visceral and parietal pleura. Of course, an intervention is needed to reduce the risk of inflammation, one of which is by using a pleurodesis agent, which has an anti-inflammatory effect. This study aimed to compare the efficacy of povidone-iodine compared to bleomycin as a pleurodesis agent in malignant pleural effusion patients at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Methods: Prospective cohort study, where as many as 46 research subjects participated in this study and were grouped into groups that received povidone-iodine and bleomycin. The success of pleurodesis agents was assessed by the production of WSD. Data analysis was carried out using SPSS univariate and bivariate. Results: The results of the study showed that there was no statistical difference between the 10% povidone-iodine agent and the bleomycin agent, where p>0.05. However, in the 10% povidone-iodine group, the success rate was 100%, while in the bleomycin group, the success rate was 82.6%. Conclusion: There was no significant difference in the efficacy of povidone-iodine as a pleurodesis agent compared to bleomycin in patients with malignant pleural effusion at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.